Activation of nuclear factor kappa B in peripheral blood mononuclear cells from malaria patients - Punsawad Chuchard; Krudsood Srivicha; Maneerat Yaowapa; Chaisri Urai; Tangpukdee Noppadon; Pongponratn Emsri; Nantavisai Kwannan; Udomsangpetch Rachanee; Viriyavejakul Parnpen (Malaria Journal, 2012)
Abstract Background Malaria parasites and their products can activate a specific immune response by stimulating cytokine production in the host’s immune cells. Transcription nuclear factor kappa B (NF-κB) is an important regulator for the control of many pro-inflammatory genes, such as interleukin-1 (IL-1) and tumor necrosis factor (TNF). The activation and expression of NF-κB p65 in peripheral blood mononuclear cells (PBMCs) of malaria patients were investigated and correlated with the levels of IL-10 and TNF to study the nature of NF-κB p65 and its linkage to inflammatory cytokines. Methods The sample group comprised 33 patients admitted with malaria caused by Plasmodium vivax (n = 11), uncomplicated Plasmodium falciparum (n = 11), and complicated Plasmodium falciparum (n = 11). Peripheral blood was collected at admission and on day 7 for PBMC isolation. Healthy subjects were used as a control group. The expressions of NF-κB p65 in the PBMCs from malaria patients and the plasma levels of IL-10 and TNF were measured by using enzyme-linked immunosorbent assay (ELISA). The immunofluorescence technique was used to determine NF-κB nuclear translocation. Results At admission, patients with P. vivax and uncomplicated P. falciparum had significantly elevated phospho-NF-κB p65 levels in the PBMCs compared with those of healthy controls. However, patients with complicated P. falciparum malaria had decreased levels of phospho-NF-κB p65. On day 7 post-treatment, significantly increased phospho-NF-κB p65 was found in the PBMCs of patients with complicated P. falciparum, compared with healthy controls. The plasma level of IL-10 was elevated in day 0 in patients with complicated P. falciparum malaria and was found to be negatively correlated with phospho-NF-κB p65 level (rs = −0.630, p = 0.038). However, there was no correlation between phospho-NF-κB p65 expression and TNF level in patients with complicated P. falciparum malaria. Conclusions This is the first report demonstrating alterations in NF-κB p65 activity in the PBMCs of malaria patients. The altered lower features of NF-κB p65 in the PBMCs of patients with complicated P. falciparum at admission could be due to a suppressive effect of high IL-10 associated with complicated P. falciparum malaria.